1982
DOI: 10.1037/0022-006x.50.5.643
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of behavior problems in Anglo-American and Mexican-American preschool children: A comparative study.

Abstract: This study compared the factor structure of a modified Behavior Problem Checklist for groups of Mexican-American (MA) and Anglo-American preschool children from low-socioeconomic-class families. Of the five factors extracted for each group, only the Anxiety-Withdrawal dimension exhibited strong cross-cultural similarity. Two other MA factors, Distractible-Hypoactive and Anxious-Negativism, were interpretable within the framework of MA culture. These results suggest that emergent classification systems should a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Most of the studies investigating the relationship between trait anxiety or psychopathological symptoms, however, are based on data obtained from the parents (cf. [1,2,6,[20][21][22]25]). Mindell and Barrett [23], for example, demonstrated that the relationship between trait anxiety and nightmare frequency was only present in the data reported by the children but not in the data reported by the parents; a finding that might be associated with the underestimation of nightmare occurrence in parents.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies investigating the relationship between trait anxiety or psychopathological symptoms, however, are based on data obtained from the parents (cf. [1,2,6,[20][21][22]25]). Mindell and Barrett [23], for example, demonstrated that the relationship between trait anxiety and nightmare frequency was only present in the data reported by the children but not in the data reported by the parents; a finding that might be associated with the underestimation of nightmare occurrence in parents.…”
Section: Introductionmentioning
confidence: 99%
“…Of the few previously published studies on behavior problems during early childhood among Hispanic children, only two involved relatively large samples (e.g., more than 60 participants) (Ispa et al, 2004; O’Donnell et al, 1982), and only three (Gamble & Modry-Mandell, 2008; Ispa et al, 2004; La Roche et al, 1995) utilized a longitudinal design. There is a clear need for more information on problem behavior development in this rapidly growing demographic group.…”
Section: Discussionmentioning
confidence: 99%
“…, symptom rates) have been consistently reported in the literature for Mexican-Americans (e.g., Fabrega, Rubel, & Wallace, 1967;Meadow & Stoker, 1965;Meadow, Stoker, & Zurcher, 1967;O'Donnell, Stein, Machabanski, & Cress, 1982;Stoker & Meadow, 1974;Touliatos & Lindholm, 1976;Trevino & Bruhn, 1977;Wignall & Koppin, 1967). Sex-related differences have also been reported on standard epidemiological measures of psychopathology (e.g., Golding & Karno, 1988;Roberts & Roberts, 1982;Vega, Kolody, & Warheit, 1985;Vega, Warheit, Buhl-Auth, & Meinhardt, 1984;Warheit, Vega, Auth, & Meinhardt, 1985).…”
mentioning
confidence: 79%